Mapping archaeological landscapes in transformation : a chaîne-opératoire approach (2019)
Inevitably, archaeology has had something to do with landscapes, ever since the early days of the discipline. In every stage of its development, encompassing or smallish, this relationship has been (de/re-)constructed and (pre/re/post-) conceived. Since the 1990s, the idea of landscape has once again become prom- inent in archaeology, serving often as an interface between the physical and the conceptual, the spatial and the social, the real and the image, the natural and the cultural (David and Thomas 2016). Archaeological landscapes, however, have served less as an interactive field between these sets of concepts — that typically oppose one another in modernist thinking — functioning more as a common boundary between them. Specifically, remote sensing, photogramme- try, surveying, cartography, and GIS-based methods (mainly cost-distance and visibility analysis) have broadly constituted the empirical and positivist approach to archaeological landscapes, concentrating on the natural and physical aspects (Bevan and Conolly 2004; Hritz 2014; Sevara et al. 2017).